Challenges of schooling in ethnically divided post-conflict communities: research findings and policy recommendations - Čorkalo Biruški, Dinka (Array, 2011)
The experiences of post-conflict societies show that the process of trust building and normalization of social life is slower and more demanding than the material renewal. This process is especially difficult in divided communities where ethnicity plays a key role in shaping community social dynamics. As a result of the recent war, the city of Vukovar (Croatia) turned into the ethnically divided community where even schools became divided along the ethnic lines. By being divided in the schools and not encouraged to communicate outside the school, children are prevented from having contacts, which is a basic condition for normalization of inter-group relations. The present study explores a set of intergroup attitudes in the context of separate schooling: (1) attitudes towards school integration ; (2) attitudes toward social integration of children outside the schools ; (3) tolerance of diversity ; (4) attitudes toward assimilation of ethnic minorities ; (5) contacts with outgoup, and (6) tendency to discriminate the outgoup members. The study was conducted in 2001 and 2007 with school children of Croatian (majority) and Serbian (minority) ethnic background (N= 719 and N= 815) aged 12-16 and their parents. Results revealed different pattern of attitudes depending on the majority and minority status at both time points, but also depending on the social role of the participants, with parents having more positive intergroup attitudes. Our results also show only minor improvements of intergroup attitudes among children over the period of six years, indicating potentially detrimental effects of social division and separate schooling on young people’s inter-ethnic relations. The possibility of schools serving as an integrative social factor in the post-conflict society will be discussed.